2012
DOI: 10.4314/ajcem.v14i1.2
|View full text |Cite
|
Sign up to set email alerts
|

PCR Detection of <i>Entamoeba histolytica</i> in Microscopically Positive Stool Samples of Hospital Patients in Soroti, Eastern Uganda

Abstract: Amoebiasis is an infection caused by water borne protozoan parasite Entamoeba histolytica. In Uganda where sanitation infrastructure and health education was not adequate, amoebiasis was thought to be still an important health problem. However there was little or no data on prevalence of this very important protozoan infection. In addition, microscopy remained the main method for the diagnosis of amoebiasis but could not differentiate between Entamoeba dispar/moshkovskii and Entamoeba histolytica infections. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
3
4
0
Order By: Relevance
“…This observation compares well with results obtained in a similar study conducted in northern Ghana by (68&70) ,that showed a high prevalence (9.8%) of E. histolytica/dispar complex by microscopy and 8.8% of Entamoeba dispar but only one case of Entamoeba histolytica by PCR. These results agree with Samuel Ekuban (15) in North District of the Ashanti Region. In consonance with other studies (33) .…”
Section: Resultssupporting
confidence: 89%
“…This observation compares well with results obtained in a similar study conducted in northern Ghana by (68&70) ,that showed a high prevalence (9.8%) of E. histolytica/dispar complex by microscopy and 8.8% of Entamoeba dispar but only one case of Entamoeba histolytica by PCR. These results agree with Samuel Ekuban (15) in North District of the Ashanti Region. In consonance with other studies (33) .…”
Section: Resultssupporting
confidence: 89%
“…This observation compares well with results obtained in a similar study conducted in northern Ghana by (68&70) ,that showed a high prevalence (9.8%) of E. histolytica/dispar complex by microscopy and 8.8% of Entamoeba dispar but only one case of Entamoeba histolytica by PCR. These results agree with Samuel Ekuban (15) in North Z.U.M.J.Vol.19; N.6; November; 2013 -563-…”
Section: Detection Of Human Intestinal Protozoa By ……supporting
confidence: 82%
“…Amoebiasis was also diagnosed mostly using Kato-Katz method. Prevalence estimates ranged from 4.6 to 15,3% in Ethiopia ( Gedle et al, 2017 ; Gadisa and Jote, 2019 ; Sisay and Lemma, 2019 ), 5.9 to 58.3% in Kenya ( Kipyegen et al, 2012 ), 54.5% in Rwanda ( Niyizurugero et al, 2013 ), 0.7 to 2.7% in Sudan ( Karrar and Rahim, 1995 ), 19.93% in Uganda ( Ekou et al, 2012 ) and 4.5 to 5.0% in Seychelles ( Kitua et al, 1988 ; Albonico et al, 1996 ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the small number of studies conducted on waterborne parasitic diseases in eastern Africa over the past seven decades, available information highlights that, prevalence of important parasitic diseases is still high in recent years. These include schistosomiasis ( Rasoamanamihaja et al, 2016 ; Tadege and Shimelis, 2017 ; Won et al, 2017 ; Spencer et al, 2017 Shumbej and Girum, 2019 ), amoebiasis ( Ekou et al, 2012 ; Niyizurugero et al, 2013 ; Gedle et al, 2017 ; Gadisa and Jote, 2019 ; Sisay and Lemma, 2019 ), giardiasis ( Kipyegen et al, 2012 ; de Lucio et al, 2016 ; Gedle et al, 2017 ; Gadisa and Jote, 2019 ; Sisay and Lemma, 2019 ) and STHs ( Mwandawiro et al, 2013 ; Davis et al, 2014 ; Freeman et al, 2015 ; Emana et al, 2015 ; Tadege and Shimelis, 2017 ; Stone and Ndagijimana, 2018 ). Most of these diseases are transmitted in poor water and sanitation environments.…”
Section: Discussionmentioning
confidence: 99%